Biomass as activated carbon precursor and potential in supercapacitor applications - Rashidi, N.A. (Springer Science and Business Media Deutschland GmbH, 2022)
The continuous demand for energy coupled with environmental protection and depletion of fossil fuel has accelerated the research on electrochemical energy storage, including the supercapacitor. In context of the electrode development, activated carbon notably from biomass sources has received the utmost attention due to its renewability, low cost, apart from having an exceptional electrochemical performance. In this review, motivation for biomass utilization alongside different reactor technologies (including reactor/furnace, microwave, and hydrothermal) for the activated carbon production has been elaborated. Besides, discussion on several key characteristics (i.e., morphology, textural properties, surface wettability, and thermal strength) of activated carbon that contributes towards high supercapacitance performance along with the corresponding measurement technique has been emphasized in this manuscript. In each section, recent progress on the activated carbon production specifically from biomass that have been made in the last 10Â years (2011â2021) has been discussed. From our study on the recent publication in the last decade, reactor/furnace technology has been extensively used in both laboratory and industrial scale, whilst hydrothermal and microwave technology are the emerging technologies. In addition, both physiochemical and surface functionalities influence the electrochemical performance of the activated carbon electrode. Finally, the future work that can be incorporated while developing superior activated carbon supercapacitors has been outlined in this review paper. It is hoped that this review paper can serve as a guidance for researchers in exploring the economic and facile procedures in synthesizing the activated carbons for electrochemical supercapacitor applications. Graphical abstract: Figure not available: see fulltext.. Â© 2022, The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature.